Untargeted Metabolomics Approach of Cross-Adaptation in Salmonella Enterica Induced by Major Compounds of Essential Oils - Pamplona Pagnossa, Jorge; Rocchetti, Gabriele; Bezerra, Jadson Diogo Pereira; Batiha, Gaber El-Saber; El-Masry, Eman A.; Mahmoud, Mohamed H.; Alsayegh, Abdulrahman A.; Mashraqi, Abdullah; Cocconcelli, Pier Sandro; Santos, Cledir; Lucini, Luigi; Hilsdorf Piccoli, Roberta (Frontiers in Microbiology, 2022)
Cross-adaptation phenomena in bacterial populations, induced by sublethal doses of antibacterial solutions, are a major problem in the food safety field. In this regard, essential oils and their major compounds appear as an alternative to common sanitizers in food industry environments. The present study aimed to evaluate the untargeted metabolomics perturbations of Salmonella enterica serovar Enteritidis previously exposed to sublethal doses of the essential oils major components: cinnamaldehyde, citral, and linalool. Cinnamaldehyde appeared as the most efficient compound in inhibitory effect assays (0.06% v/v as MBC). Also, preliminary tests exhibited a phenotype of adaptation in planktonic and sessile cells of S. Enteritidis when exposed to sublethal doses of linalool, resulting in tolerance to previous lethal concentrations of citral. Metabolomics approach on S. Enteritidis exhibited an important insight over cross-adaptation induced by sublethal doses of major compounds of some essential oils. In addition, according to results obtained, when using single molecules many pathways may be involved in bacterial tolerance, which could be different from what was revealed in previous studies about the use of phytocomplex of essential oils. Orthogonal projection to latent structures (OPLS) proved to be an interesting predictive model for adaptation events in pathogenic bacteria because of global engagement for preventing and controlling foodborne outbreaks.